Muscle wasting in the critically ill patient: how to minimise subsequent disability. (2nd April 2020) - Flower, Luke; Puthucheary, Zudin
Abstract : Muscle wasting in critically ill patients is the most common complication associated with critical care. It has significant effects on physical and psychological health, mortality and quality of life. It is most severe in the first few days of illness and in the most critically unwell patients, with muscle loss estimated to occur at 2–3% per day. This muscle loss is likely a result of a reduction in protein synthesis relative to muscle breakdown, resulting in altered protein homeostasis. The associated weakness is associated with in an increase in both short- and long-term mortality and morbidity, with these detrimental effects demonstrated up to 5 years post discharge. This article highlights the significant impact that muscle wasting has on critically ill patients' outcomes, how this can be reduced, and how this might change in the future.